2016
DOI: 10.18632/oncotarget.9280
|View full text |Cite
|
Sign up to set email alerts
|

Tailored chemokine receptor modification improves homing of adoptive therapy T cells in a spontaneous tumor model

Abstract: In recent years, tumor Adoptive Cell Therapy (ACT), using administration of ex vivo-enhanced T cells from the cancer patient, has become a promising therapeutic strategy. However, efficient homing of the anti-tumoral T cells to the tumor or metastatic site still remains a substantial hurdle. Yet the tumor site itself attracts both tumor-promoting and anti-tumoral immune cell populations through the secretion of chemokines. We attempted to identify these chemokines in a model of spontaneous metastasis, in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…The expression of integrin αvβ3 correlated with disease progression in various type of cancer, including breast, pancreatic and prostate cancer and glioblastomas [ 43 49 ]. Given its role in cancer progression and neo-angiogenesis processes, it is not surprising that integrin αvβ3 represents an interesting target for the visualization and treatment of a variety of tumors [ 15 , 40 , 50 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of integrin αvβ3 correlated with disease progression in various type of cancer, including breast, pancreatic and prostate cancer and glioblastomas [ 43 49 ]. Given its role in cancer progression and neo-angiogenesis processes, it is not surprising that integrin αvβ3 represents an interesting target for the visualization and treatment of a variety of tumors [ 15 , 40 , 50 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, attempts have been made to correct this mismatch by engineering T cells with receptors for chemokines or cytokines abundant in the TME, showing preliminary encouraging results. In TRAMP mice with metastatic prostate adenocarcinoma expressing high levels of CCL2, the expression of CCR2 in SV40 Tag-specific CD8 lymphocytes increased T cell homing to the tumor (321). In xenograft models, T cell transduction with a RV encoding CX3CR1 enhanced migration toward human cell lines expressing Fractalkine, the CX3CL1 ligand, and inhibited tumor growth (322).…”
Section: Enforcing Chemokine Receptor Expression In T Cellsmentioning
confidence: 99%
“…Such events clearly happen away from the clinically observable conditions of cancer patients, whose diagnosis occurs long after the carcinogenic event; this may be limiting the incentive to study the role of Treg cells in carcinogenesis. Yet even in growing tumors, evidence has shown that formation of tumor-promoting fibrotic capsules around prostate tumors occurs only in the presence of pro-inflammatory T cells (40), selective suppression of which would be beneficial.…”
Section: Treg and Cancermentioning
confidence: 99%